Ecosistema fintech en Colombia (2022)
This monograph will analyze the economic and social impact of the entry of companies that offer their financial services, through the development of virtual platforms and tools, supported by the fields of mobile internet, big data, blockchain, the cloud and artificial intelligence, facilitating the action and interaction between the entity and the clients, allowing a greater segment of society to be covered and banked. On the other hand, it is also intended to understand both the impact that the entry of this competition in the financial market will generate, as well as the benefits, advantages and risks intrinsic to this type of platform. The study will be carried out through an exploratory model in which information recorded in research works, scientific articles and web platforms will be taken, with the aim of interweaving the information found in an organized manner, without its own conclusions and presenting new results that They allow us to detect the impact that Fintech has had in Colombia and its characteristics. Similarly, in the study it was noted that the global pandemic situation due to covid-19 potentiated a general need to use this type of platform to meet financial demands, as well as the purchase of goods and services, making the market of companies providing financial services (Fintech), increase and consolidate globally. However, this growth of the Fintech industry can bring with it financial risks, due to the lack of strict controls that monitor these accelerated entities, as well as the handling that they give to the financial information of their clients.